EU VAT at the dawn of the Fourth Industrial Revolution*. (3rd July 2018) - Beretta, Giorgio
ABSTRACT: The Fourth Industrial Revolution is in full swing. Advances in robotics and artificial intelligence, the ubiquitous presence of Big Data, and the increased reliance on cloud computing are just some glimpses of how technological innovation is re-shaping today's society and the economy, thus bridging the gap between the digital and physical spheres. Using a traditional method of jurisprudence, which involves the joint examination of various legal materials, such as legislation, case law, institutional sources of interpretation, and scholarly opinions, the article examines, in turn, the main challenges or, at least, the potential threats that the on-going transformation in each of those areas poses or might pose in the near future to the application of the current European VAT rules. Based on such analysis, the author submits that the current EU VAT system is generally well-equipped to cope with the on-going transformation, especially with regard to the advent of cloud computing technologies. Nonetheless, a few minor 'fixes' to the existing rules or, at least, a clarification of their interpretation could be conceived in other areas subject to the present technological developments. In particular, adjustments to current EU VAT rules can be provided as to take into account the increased capability of robots to operate completely autonomously, which might ultimately lead them to acquire the status of 'taxable persons', or also in view of the sensational ability shown by digital firms in monetising and commercially exploiting user data, which often constitute the sole 'consideration' paid by individuals in digital barter transactions.